Utilization of Multimedia in Student News Video Projects on Praktik Jurnalistik Media Televisi Course - Yusandra, Titiek Fujita; Haslina, Welsi (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
This article aims to explain the use of multimedia in the form of the kinemaster application in the learning process of making news videos in the Praktik Jurnalistik Media Televisi course. The method used is a descriptive method with a qualitative approach. Data were collected from field findings, participant data, and researcher reflections. Sources of data obtained from direct experience, the results of interviews, observations, and documentation from lecturers who are in charge of the Praktik Jurnalistik Media Televisi course at the Indonesian Language and Literature Education Study Program, STKIP PGRI Sumatera Barat. Based on the findings, the kinemaster application helps students in producing news videos. After the data, news scripts, and voices that have been recorded are complete, they take advantage of this application to combine video, sound and images. This application provides a fairly complete video editing feature and can directly edit it on the spot without having to move to another application. Thus, the use of learning resources in the form of multimedia applications in the Praktik Jurnalistik Media Televisi will increase the effectiveness of learning, so that learning becomes more meaningful for students to get direct experience in the use of technology.